New insights in the flavor and chemistry of Huanglongbing tolerant citrus hybrids with/without Poncirus trifoliata in their pedigree - Jeffries, Kristen A.; Fan, Zhen; Sun, Xiuxiu; Olmedo, Gabriela M.; Zhao, Wei; Mattia, Matthew; Stover, Ed; Baldwin, Elizabeth; Manthey, John A.; Breksa, Andrew; Bai, Jinhe; Plotto, Anne (Frontiers in Horticulture, 2024)
Citrus hybrids with Poncirus trifoliata L. Raf. introgression have gained interest due to their tolerance to Huanglongbing (HLB), a devastating disease for Florida citrus agriculture. While these hybrids inherit disease tolerance from P. trifoliata, they sometimes also suffer from undesirable offflavors. A selection of thirteen genotypes were harvested over the 2020-2021 and 2021-2022 seasons. Their juices were evaluated by a trained sensory panel and were comprehensively analyzed for their chemical makeup, including soluble solids content (SSC), titratable acidity (TA), volatiles, flavonoids and limonoids. Overall, along with the commercial orange cultivars 'Valencia' and 'Hamlin', the HLB-tolerant Poncirus hybrid 'US SunDragon,' and the mandarin hybrids Sugar Belle ® , FF-5-51-2, and 'US Superna' had positive citrus flavor quality. Esters, some sesquiterpenes, along with flavonoids, eriocitrin and quercetin-3-(3R-glucosylrutinoside), were positively correlated with orange flavor while β-ionone and eucalyptol were highly abundant in the mandarins. The flavonoid linarin, was more abundant in Poncirus hybrids with off-flavors than in the Poncirus hybrid 'US SunDragon', having high orange flavor. Two mandarin hybrids, FF-5-6-36 and FTP-6- 32-67, were not bitter at harvest, but the juice exhibited delayed bitterness after storage at -20 °C, which was associated with significant increases of limonin, nomilin, naringenin, and prunin. Interestingly, during freezer storage, a newly identified flavonoid in citrus, tricin-C-hexoside, increased dramatically across all of the genotypes. The identification of disease-tolerant hybrids with satisfactory flavor quality at juicing as well as after storage where delayed bitterness may develop, has great significance for future breeding efforts for fresh fruit or for use in stand-alone juice/juice blends.